Microtexturas de reacción en zonas de blackwall, Faja Máfica-Ultramáfica del río de Las Tunas, Cordillera Frontal de Mendoza - Gargiulo, Maria Florencia (2016)
“Reaction microtextures in blackwall zones, Río de Las Tunas mafic-ultramafic belt, Cor- dillera Frontal of Mendoza”. Reaction microtextures developed in the chlorite blackwall zones located in between bodies from Río de Las Tunas mafic- utramafic belt and schist country rock were stud- ied in this contribution. The outcrops belong to the Cordillera Frontal of Mendoza province. The studied microtextures are developed in porfiroblasts com- pletely replaced by chlorite. Around these porfirob- lasts is observed a rim with microvermiform spinel s.l. aggregates in reaction with chlorite and magnetite groundmass. Small amphibole porfirob- lasts with chemical zoning is superimposed to these reaction rims. The studied microtextures can be explained by the reaction chlorite + magnetite à spinel, which indicates a relative increase in the T of the system. This increase can be related with the gondwanic magmatism developed in the area.